Multiple Personalities of The Main Character in the Novel I Don't Hate Rain Sri Puji Hartini's Works: Psychological Study of Literature - Novriyanti, Yohana; Lubis, Haris Sutan; Marsella, Emma (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research aims to analyze and describe the description of the dual personality experienced by the main character in the novel Aku Tak Membenci Hujan by Sri Puji Hartini. This research uses a qualitative descriptive method. The data in this research are in the form of words, phrases, sentences that show a picture of the dual personality of the main character in the novel Aku Tak Membenci Hujan by Sri Puji Hartini. The data source for this research is the novel Aku Tak Membenci Hujan by Sri Puji Hartini. Data collection techniques start from reading the novel repeatedly and marking and recording the data found. After data related to multiple personalities is collected, it will be applied in discussing the problem, providing solutions to the data obtained. The theory used is Siggmund Freud's Psychoanalysis. The results of the analysis obtained are that there is structure and a picture of multiple personalities in the characters, namely the presence of four different personality states, repetitive personalities controlling a person's behavior, there is a failure to recall important personal information that is too substantial to be considered ordinary forgetting, this disorder is not thought to occur due to the effects of substances psychoactive or general medical conditions, dissociative amnesia, and dissociative fugue.